2019
DOI: 10.1038/s41598-019-52035-6
|View full text |Cite
|
Sign up to set email alerts
|

C9orf72-generated poly-GR and poly-PR do not directly interfere with nucleocytoplasmic transport

Abstract: Repeat expansions in the C9orf72 gene cause amyotrophic lateral sclerosis and frontotemporal dementia characterized by dipeptide-repeat protein (DPR) inclusions. The toxicity associated with two of these DPRs, poly-GR and poly-PR, has been associated with nucleocytoplasmic transport. To investigate the causal role of poly-GR or poly-PR on active nucleocytoplasmic transport, we measured nuclear import and export in poly-GR or poly-PR expressing Hela cells, neuronal-like SH-SY5Y cells and iPSC-derived motor neur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
50
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(61 citation statements)
references
References 55 publications
9
50
1
Order By: Relevance
“…mRNA containing the pathological G4C2 expansion has been shown to form stable Gquadruplexes in the nucleus that retain RNA binding proteins and induce splicing defects (Cooper-Knock et al, 2014;Donnelly et al, 2013;Gitler & Tsuiji, 2016;Haeusler et al, 2014;Sareen et al, 2013;Simon-Sanchez et al, 2012;Xu et al, 2013). R-DPRs have been additionally shown to interact with membrane-free phase separated compartments, such as the nucleolus, causing nucleolar stress and dysfunction of nucleolar quality control, as well as impairment of nucleocytoplasmic trafficking (Frottin et al, 2019;Hayes et al, 2020;Kwon et al, 2014;Lee et al, 2016;Mizielinska et al, 2017;Shi et al, 2017;Tao et al, 2015;Vanneste et al, 2019;White et al, 2019). Additionally, cytoplasmic poly-GA aggregates associate extensively with proteasomes, interfere with proteasome activity (Guo et al, 2018), and have been found to colocalize with p62, ubiquitin and several components of the proteasome machinery in patient brain (Al-Sarraj et al, 2011;Guo et al, 2018;May et al, 2014;.…”
Section: Both Loss-and Gain-of-function Mechanisms Have Been Suggestementioning
confidence: 99%
“…mRNA containing the pathological G4C2 expansion has been shown to form stable Gquadruplexes in the nucleus that retain RNA binding proteins and induce splicing defects (Cooper-Knock et al, 2014;Donnelly et al, 2013;Gitler & Tsuiji, 2016;Haeusler et al, 2014;Sareen et al, 2013;Simon-Sanchez et al, 2012;Xu et al, 2013). R-DPRs have been additionally shown to interact with membrane-free phase separated compartments, such as the nucleolus, causing nucleolar stress and dysfunction of nucleolar quality control, as well as impairment of nucleocytoplasmic trafficking (Frottin et al, 2019;Hayes et al, 2020;Kwon et al, 2014;Lee et al, 2016;Mizielinska et al, 2017;Shi et al, 2017;Tao et al, 2015;Vanneste et al, 2019;White et al, 2019). Additionally, cytoplasmic poly-GA aggregates associate extensively with proteasomes, interfere with proteasome activity (Guo et al, 2018), and have been found to colocalize with p62, ubiquitin and several components of the proteasome machinery in patient brain (Al-Sarraj et al, 2011;Guo et al, 2018;May et al, 2014;.…”
Section: Both Loss-and Gain-of-function Mechanisms Have Been Suggestementioning
confidence: 99%
“…Our work does not exclude other -ribosome-independent-mechanisms that may contribute to C9ORF72-ALS/FTD, including: defective nuclear transport (Shi et al, 2017;Vanneste et al, 2019), defective splicing (Kwon et al, 2014;Yin et al, 2017), aggregation of non-arginine DPRs, such as poly-GA (Guo et al, 2018), repeat-RNA toxicity, or loss of functional C9ORF72 protein and more (as reviewed in refs (Balendra and Isaacs, 2018;Gitler and Tsuiji, 2016)). Yet, concrete structural mechanisms of macromolecular inhibition for these possible pathways remain to be determined.…”
Section: Discussionmentioning
confidence: 97%
“…Poly(PR) and poly(GR) were also found to interact with RNA binding proteins and other low complexity domain proteins, including those in the nuclear pore complex (Lee et al, 2016) and using Xenopus laevis oocytes, poly(PR) was shown to bind and block the central channel of the pore (Shi et al, 2017). However, in the SHSY-5Y neuronal cell line and iPSC-derived neurons, it was shown that poly(GR) and poly(PR) had no effect on active nucleocytoplasmic transport, though poly(GA) deficits were observed (Vanneste et al, 2019). Thus, there are likely to be specific pathogenic mechanisms associated with the different DPRs.…”
Section: Toxicity By Dprmentioning
confidence: 99%